(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article discusses the features of modeling classes in a modern school based on innovative pedagogical technologies. The author analyzes the need for transition to student-centered learning, the use of game, project, communicative, information and communication and health-saving technologies. It is shown that the introduction of innovative technologies contributes to the development of cognitive activity of schoolchildren, strengthening their independence and the formation of readiness for lifelong learning.